2018
DOI: 10.1177/0218492318810647
|View full text |Cite
|
Sign up to set email alerts
|

Systemic ventricle morphology impact on ten-year survival after Fontan surgery

Abstract: Background The Fontan procedure has been applied in many patients with single-ventricle physiology, with quite low mortality rates all over the world, and a 8.6%–9.1% rate in Indonesia. Structural and characteristic differences in the morphologically left and right ventricles influence the role of the systemic ventricle in the functionally univentricular heart and impact on postoperative outcomes. Mid- and long-term survival based on systemic ventricle morphology remains controversial. This study aimed to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…No differences in mortality were demonstrated in these patients at the time of transplantation. While the morphology of the systemic ventricle is associated with immediate mortality at the time of cavopulmonary bypass, no differences in the presentation of HF or other failures have been demonstrated when comparing a right or left morphology of the single ventricle [106,107]. Variables such as hospitalizations due to HF or sudden death events are directly associated with mortality in transplant patients [108], and these variables were not controlled in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in mortality were demonstrated in these patients at the time of transplantation. While the morphology of the systemic ventricle is associated with immediate mortality at the time of cavopulmonary bypass, no differences in the presentation of HF or other failures have been demonstrated when comparing a right or left morphology of the single ventricle [106,107]. Variables such as hospitalizations due to HF or sudden death events are directly associated with mortality in transplant patients [108], and these variables were not controlled in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Previously known myocardial dysfunction or atrioventricular valve insu ciency was not observed in the patients who were lost. In a 10-year study by Mira Fauziah et al systemic ventricular morphology was not associated with the 10-year survival rate after Fontan surgery (14). The probable cause was the problem of meeting the systemic venous return by the pulmonary system, diameter mismatch or increased pulmonary vascular resistance.…”
Section: Discussionmentioning
confidence: 94%
“…Patients who met the inclusion criteria were divided into two different groups; age at Fontan completion (operation) < 6 and ≥ 6 years old. This age cutoff was based on a previous average age for Indonesian Fontan patients by Fauziah et al [ 10 ]. Clinical follow-up was completed by medical record review, phone calls, or mails.…”
Section: Methodsmentioning
confidence: 99%
“…Some experts argue that postponing Fontan completion could delay the onset of Fontan complications. Fauziah et al reported that most patients who underwent Fontan completion in Indonesia were older than patients in developed countries, with a median age of 6 years (range 3–22 years) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%